Efektivitas Intervensi Motor Imagery (MI) terhadap Rehabilitasi Pasien Post stroke: A Systematic Review - Bernadetta Germia Aridamayanti; Gevi Melliya Sari; Wimar Anugrah Romadhon (FORIKES, 2020)
Background: Motor Imagery (MI) is an intervention to improve motor skills in post stroke hemiparesis patients by focusing on weak body parts. Objective: To describe the effectiveness of providing MI in the rehabilitation of post stroke patients. Method: The database used to identify suitable articles obtained from Scopus, ProQuest and Pubmed was limited to the last 5 years of publication from 2016 to 2020, English, and fulltext articles. The literature review used the keyword